Characterisation of graphene fibres and graphene coated fibres using capacitively coupled contactless conductivity detector. Issue 9 (25th February 2016) - Cabot, Joan M.; Duffy, Emer; Currivan, Sinéad; Ruland, Andres; Jalili, Rouhollah; Mozer, Attila J.; Innis, Peter C.; Wallace, Gordon G.; Breadmore, Michael; Paull, Brett
Abstract : The use of capacitively coupled contactless conductivity detection (C 4 D) for the characterisation of thin conductive graphene fibres, graphene composite fibres, and graphene coated fibrous materials is demonstrated for the first time. Abstract : The use of capacitively coupled contactless conductivity detection (C 4 D) for the characterisation of thin conductive graphene fibres, graphene composite fibres, and graphene coated fibrous materials is demonstrated for the first time. Within a few seconds, the non-destructive C 4 D detector provides a profile of the longetudinal physical homogeneity of the fibre, as well as extra information regarding fibre mophology and composition. In addition to the theoretical considerations related to the factors affect the output signal, this work evaluates the properties of graphene fibres using scanning C 4 D following the manufacturing process of wet-spinning. Furthermore, conductive graphene-coated fibrous materials and the effectiveness of the coating and reduction procedures applied could be investigated. Apart from the application of C 4 D in the monitoring of such processes, the feasibility of this small, highly sensitive and rapidly-responsive detector to monitor strain and elasticity responses of conductive and elastomeric composite fibres for applications in motion sensing, biomedical monitoring, and stretchable electronics was also demonstrated.